Religious Dynamics and Traditional Beliefs in the Ruwat Laut Ritual Amidst the Pandemic Crisis - Sidik, Mohamad Dindin Hamam (Journal of Contemporary Rituals and Traditions, 2023)
This article delves into the profound meanings of religious practices and traditional beliefs within the context of the coastal community of Waymuli Village amidst the COVID-19 pandemic crisis. Focusing on the Ruwat Laut ritual, this study analyzes how the interaction between traditional beliefs and the official religion, Islam, influences religious practices and the attitudes of the community in confronting global challenges. Through in-depth interviews with customary leaders, village heads, religious educators, farmers, and fishermen, the article reveals shifts in religious practices and the pandemic's impact on ritual implementation. The analysis results demonstrate transformations in traditional belief practices and community adaptations to changing circumstances, including social restrictions and ritual limitations. This article also discusses the factors influencing religious attitudes and practices during a crisis situation. The article's conclusion underscores the importance of gaining a deeper understanding of how communities uphold their beliefs and religious practices when facing modern challenges, while maintaining a balance between tradition and adaptation. This research contributes valuable insights to the study of religious diversity and community adaptation in the face of global crises.